Problematic Internet Use and Resilience: A Systematic Review and Meta-Analysis - Hidalgo-Fuentes, Sergio; Martí-Vilar, Manuel; Ruiz-Ordoñez, Yolanda (Nursing reports (Pavia, Italy), 2023)
Problematic Internet use has become a major problem worldwide due to its numerous negative correlates in the field of health, both mental and physical, and its increasing prevalence, making it necessary to study both its risk and protective factors. Several studies have found a negative relationship between resilience and problematic Internet use, although the results are inconsistent. This meta-analysis assesses the relationship between problematic Internet use and resilience, and analyses its possible moderating variables. A systematic search was conducted in PsycInfo, Web of Science and Scopus. A total of 93,859 subjects from 19 studies were included in the analyses. The results show that there is a statistically-significant negative relationship (r = −0.27 (95% CI [−0.32, −0.22])), without evidence of publication bias. This meta-analysis presents strong evidence of the relationship between the two variables. Limitations and practical implications are discussed.